The effect of consumer attitude towards coffee shop green practices on purchase intention / Flora Shumin Chang, Chao-Chin Liu and Chun-Yi Chang - Chang, Flora Shumin; Liu, Chao-Chin; Chang, Chun-Yi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
With the growing awareness and concerns towards environment protection and conservation, consumers nowadays are becoming more interested and more willing to buying green product even if it means paying for a higher price. Although literature supports the positive influence of consumer attitude towards green product on purchase intention, study on this subject remains scare in Malaysia. This study examined the effect of consumer attitude towards green coffee shops on purchase intention. Quantitative method was used in this study. Online survey was conducted with the questionnaire distributed via social media platforms. A total of 387 useable questionnaires, which are more than the estimated sample size of 377, were collected. The data was analyzed using SPSS. The regression analysis results showed a strong correlation between consumer attitude and purchase intention. The R2 value of 0.404 indicated that 40.4% of the variation in the dependent variable consumer’s purchase intention can be explained by the independent variable consumer’s attitude towards coffee shop green practices. The implications of the study as well as the recommendations for future research were also discussed.